Rediscovery of two rare ptilodontines in Taiwan: Himeropteryx yui Okano, 1969 stat. nov. and Ptilophora rufula Kobayashi, 1994 (Lepidoptera, Notodontidae) - Wu, Shipher; Owada, Mamoru; Fu, Chien-Ming (Zootaxa, 2013)
The notodontid genera Himeropteryx Staudindger, 1887 and Ptilophora Stephans, 1828 are both typical low-temperature flying taxa belonging to subfamily Ptilodontinae (Schintlmeister 2008). The former is a monotypic genus containing H. miraculosa Staudinger, 1887 from East Asia, and the latter encompasses six Old Word species. Ptilophora are well known Acer-feeders (Aceraceae) in the previous records (Nakatomi 1987; Schintlmeister 2008; Kobayashi 2011), while Himeropteryx miraculosa also feeds on Aesculus tuburinata (Aceraceae) and Carpinus japonica (Betulaceae) (Nakatomi, 1987). The population of Himeropteryx in Taiwan was first recorded and described by Okano (1969) as a subspecies yui of H. miraculosa based on one male specimen collected in the vicinity of Nengkuoshan (elevation ca. 3000m) in central Taiwan. Subsequently, this name combination was listed in Sugi (1992) but the reference year was erroneously cited as 1960 and no further study has corrected it. In Ptilophora, a single species, P. rufula Kobayashi, 1994, was described from Taiwan from two males (both designated as type) collected in Siyuanyakou (1800 m), northern Taiwan; no additional records have been reported since then. Based on recently collected specimens from Taiwan, we here reassess the status of yui Okano. The result suggests that the Taiwanese population should be regarded as distinct species, H. yui stat. nov. In addition, the female of P. rufula is described for the first time. Institutional acronyms are as follows: BMNH, The Natural History Museum, London; ESRI, Taiwan Endemic Species Research Institute, Jiji, Nantou; NMNS National Museum of Natural Science, Taichung; NSMT, National Museum of Nature and Science, Tsukuba; NTU, National Taiwan University, Taipei; TFRI, Insect Collection, Taiwan Forestry Research Institute, Taipei.